Modelling the coherent detection optical fibre communication system - Gregory, Christopher. (2008)
The modulation and differential detection characteristics of optical CPFSK transmission system are investigated theoretically. The error rate expressions of differentially detected CPFSK are derived and the system performance for the demodulation, including the impact of laser phase noise is analayzed.